PELIBATAN KELUARGA DALAM PROSES LITMAS SEBAGAI UPAYA MENDUKUNG PEMBIMBINGAN KLIEN - ., Whenlyngk; Saputra, Moh Fatra Junika; Nusurante, Nurul Fatima S; Putra, Dimas Febrian Dwi; Laraga, Masyitah Habillah M.S.A.; Ilmi, Musfiratul; ., Waris (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to enhance active family involvement in the Community Research (Litmas) process as an effort to support the guidance of correctional clients at the Class I Correctional Center (Bapas) of Palu. The identified problem is that the role of families in the Litmas process remains limited, as families tend to function merely as formal guarantors and administrative data providers rather than active partners in the client guidance process. This activity was conducted through a descriptive qualitative approach based on community service, employing in-depth interviews with Community Supervisors and clients' families, as well as direct orientation sessions delivered to families during the Litmas process, in line with the mandate of Law Number 22 of 2022 on Corrections, which stipulates that correctional guidance shall be implemented through accompaniment, counseling, and supervision to prepare clients for social reintegration. The results indicate that family involvement in the Litmas process has not yet been running optimally, as not all guarantors are core family members who deeply understand the client's condition, supervision remains weak due to distance and time constraints, and no standardized mechanism exists for sustained family involvement beyond the Litmas schedule. Through the orientation sessions, families demonstrated improved understanding of their active role as guidance partners, and Community Supervisors confirmed that active family involvement positively impacts client behavioral change. This activity recommends strengthening intensive and sustainable family-based approaches by Community Supervisors to improve guidance effectiveness and correctional clients' social reintegration.